Robust Extraction of Soil Characteristics Using Landsat 8 OLI/TIRS - Thanh-Van Hoang; Tien-Yin Chou; Yao-Min Fang; Chun-Tse Wang; Ching-Yun Mu; Nguyen Quang Tuan; Do Thi Viet Huong; Ha Van Hanh; Doan Ngoc Nguyen Phong (Remote Sensing, 2022)
This research utilized various methods for extracting soil characteristics from Landsat 8 OLI/TIRS imagery in the Thua Thien Hue province, Vietnam. In this study, the Object-Based Oriented Classification (OBOC) method was used to extract information about land cover (focusing on rock outcrops) on the basis of the TGSI, NDVI, and NDBI indicators. The soil moisture information was determined by examining the correlation between the Land Surface Temperature (LST) and the Normalized Difference Vegetation Index (NDVI). The findings indicated that 40 locations in the study area were covered with rock outcrops, with a Kappa index of 85.10%. In addition, soil moisture varied markedly from the sandy coastal regions, urban areas, and hilly and mountainous areas on the study area’s surface. The extracted soil information can serve as a foundation for local socio-economic development planning.